Răspuns :
= [ ( m + n) ³ · ( -1) ³ · ( m -n ) ³ · ( a -b) ²· ( a + b) ² ] / supra
/ [( a +b) ³ · ( a - b ) ³· ( m -n) ² · ( m +n ) ² ]
( -1 ) ³ = - 1
= - [ ( m +n) · ( m -n) ] / [ ( a +b) ·( a - b) ]
/ [( a +b) ³ · ( a - b ) ³· ( m -n) ² · ( m +n ) ² ]
( -1 ) ³ = - 1
= - [ ( m +n) · ( m -n) ] / [ ( a +b) ·( a - b) ]
(m+ n)³ · (m- n)³ · (a²- b²)² = m+n= a m-n= b a³·b³=(a·b)³
(a+ b) (a- b) (m²- n²) a+b= x a- b= y x³·y³=(x·y)³
[ (m+n)(m-n)]³· [(a²-b²)(a²-b²) ] =
[(a+b)(a-b)] [(m²-n²)(m²-n²)]
(m²-n²)³ · [(a²-b²)(a²-b²) ] =
(a²-b²) [(m²-n²)(m²-n²)]
(m²-n²)·(m²-n²)·(m²-n²) · (a²-b²)(a²-b²) =
(a²-b²)·(a²-b²)· (a²-b²) (m²-n²)(m²-n²)
(m²-n²)
(a²-b²)
(a+ b) (a- b) (m²- n²) a+b= x a- b= y x³·y³=(x·y)³
[ (m+n)(m-n)]³· [(a²-b²)(a²-b²) ] =
[(a+b)(a-b)] [(m²-n²)(m²-n²)]
(m²-n²)³ · [(a²-b²)(a²-b²) ] =
(a²-b²) [(m²-n²)(m²-n²)]
(m²-n²)·(m²-n²)·(m²-n²) · (a²-b²)(a²-b²) =
(a²-b²)·(a²-b²)· (a²-b²) (m²-n²)(m²-n²)
(m²-n²)
(a²-b²)